OPTIMIZING HUMAN-COMPUTER INTERACTION THROUGH SPEECH-TO-TEXT TECHNOLOGY INTEGRATION IN WEB APPLICATION INTERFACES - Sugiyarto, Muhammad Faturrohman; Setyawan, Faizal Gani; Setiawan, Hermawan (Jurnal Review Pendidikan dan Pengajaran, 2024)
In the digital era, the quality of Human-Computer Interaction (HCI) significantly influences User Experience (UX) across various applications. Developers are increasingly exploring innovative solutions such as Speech-to-Text (STT) technology(3), which allows users to interact with applications using natural language. This offers a more intuitive and efficient communication method compared to traditional input methods like typing or clicking. This integration promises to revolutionize HCI by enhancing accessibility, productivity, and user satisfaction across various application domains(1). However, implementing STT in web-based application interfaces requires further exploration due to the widespread presence and accessibility of web applications, which serve as crucial mediums for digital interactions including e-commerce, social networking, productivity tools, and entertainment platforms. This paper explores the integration of STT technology in web application interfaces, including Voxpow.com and Google Assistant, focusing on its impact on usability, user engagement, and overall HCI efficiency. By analyzing user interactions with web applications featuring STT capabilities, we aim to identify specific advantages and challenges associated with this technology. Through empirical research and user testing, we provide insights that inform future web interface design and development, ultimately enhancing user experience and driving innovation in HCI practices(2).